2006
DOI: 10.1111/j.1399-5618.2006.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective predictors of suicide and suicide attempts in 1,556 patients with bipolar disorders followed for up to 2 years

Abstract: These results indicate that patients with bipolar disorder who present with a history of SAs are over four times as likely to have a subsequent SA or completion. Further studies are needed to evaluate and prevent future attempts in this high-risk cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 42 publications
8
91
2
6
Order By: Relevance
“…Factors reported to be significantly associated with suicidal attempt include female sex, younger age of illness onset, depressive polarity of first illness episode, depressive polarity of current or more recent episode, comorbid anxiety disorder, comorbid SUD, comorbid cluster B/borderline personality disorder, first‐degree family history of suicide, and previous suicide attempts. Only male sex and first‐degree family history of suicide have been significantly associated with suicide deaths 50, 51. The periods during and following hospital admission further represent times of particularly high risk, with 14% of suicides occurring during an inpatient stay and another 26% within 6 weeks of discharge 47, 52…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…Factors reported to be significantly associated with suicidal attempt include female sex, younger age of illness onset, depressive polarity of first illness episode, depressive polarity of current or more recent episode, comorbid anxiety disorder, comorbid SUD, comorbid cluster B/borderline personality disorder, first‐degree family history of suicide, and previous suicide attempts. Only male sex and first‐degree family history of suicide have been significantly associated with suicide deaths 50, 51. The periods during and following hospital admission further represent times of particularly high risk, with 14% of suicides occurring during an inpatient stay and another 26% within 6 weeks of discharge 47, 52…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…34 Marangell et al, in a sample of 1,556 individuals with bipolar I and bipolar II, also showed that previous attempters reported more suicidal ideation at baseline and an increased risk for suicide attempts during follow-up. 35 Studies have also suggested that suicidal ideation is mostly associated with depressive and mixed episodes, 20,22 indicating that suicidal ideation can vary across different mood states. In a second analysis of the same sample during different episodes, Valtonen et al found marked differences regarding the level of.…”
Section: Stress-diathesis Modelmentioning
confidence: 99%
“…Both above mentioned disorders, have been associated with increased risk for suicide (Rihmer 2007). Patients with BD have a suicide rate 30 times higher than the general population and 25-50% of these patients will attempt suicide once in their lifetime (Marangell et al 2006). Fifteen percent of those who attempted suicide eventually make complete suicide (Izci et al 2016).…”
Section: Introductionmentioning
confidence: 99%